THE APPLICATION OF SCOR MODEL TO INCREASE EXPORT PERFORMANCE OF DURIAN EXPORT IN THAILAND - Tongmak, Thaniya; Wararatchai , Preecha (RMUTT Global Business and Economics Review, 2023)
The application of the SCOR model to improve export efficiency in Thailand to develop and monitor the underlying cause of operation of the supply chain, competitiveness and external factors that influence export performance of Thai durian with a competitive advantage as a central variable. This research is volume research. The research is 400 entrepreneurs of durian export registered with Ministry of Commerce using 20 times criteria, specific variables, data collection, questionnaire data and data analysis. Acceptable levels of consistent model with index values 2 = 52.428, df = 57, p-value = 0.647, 2/df = 0.920, AGFI = .959, GFI = 0.985, CFI = 1.000, RMSEA = 0.000 and RMR = 0.005. The most effective influence on exports of durian in Thailand is that supply chain operations have a direct, positive, and even positive influence of 0.254 are external factors. Positive direct influence of 0.212 and competitive factors have significant positive, direct, positive, 0.212 influence on a level 0.05; external factors are also found to be external. There is a significant positive 0.216 indirect influence on a level 0.05 with supply chain operations and competitive advantage as a barrier to increasing export performance in Thailand. Therefore, increasing export efficiency will be important to supply chain operations and external factors. Development, improvement, and competitive advantage should be developed, especially by bringing technology innovation to a different level of cost, service, management, flexibility to manage the entire supply chain of exports to enhance the export performance of the country's durian.